Stick-Slip Motion of Moving Contact Line on Chemically Patterned Surfaces (Communications in Computational Physics, 2010)
Based on our continuum hydrodynamic model for immiscible two-phaseflows at solid surfaces, the stick-slip motion has been predicted for moving contactline at chemically patterned surfaces [Wang et al., J. Fluid Mech., 605 (2008), pp. 59-78].In this paper we show that the continuum predictions can be quantitatively verifiedby molecular dynamics (MD) simulations. Our MD simulations are carried out fortwo immiscible Lennard-Jones fluids confined by two planar solid walls in Poiseuilleflow geometry. In particular, one solid surface is chemically patterned with alternatingstripes. For comparison, the continuum model is numerically solved using materialparameters directly measured in MD simulations. From oscillatory fluid-fluidinterface to intermittent stick-slip motion of moving contact line, we have quantitativeagreement between the continuum and MD results. This agreement is attributed tothe accurate description down to molecular scale by the generalized Navier boundarycondition in our continuum model. Numerical results are also presented for therelaxational dynamics of fluid-fluid interface, in agreement with a theoretical analysisbased on the Onsager principle of minimum energy dissipation.